2016
DOI: 10.1371/journal.pone.0146487
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Stereotype Threat Research: A Review of Psychological Mediators

Abstract: This systematic literature review appraises critically the mediating variables of stereotype threat. A bibliographic search was conducted across electronic databases between 1995 and 2015. The search identified 45 experiments from 38 articles and 17 unique proposed mediators that were categorized into affective/subjective (n = 6), cognitive (n = 7) and motivational mechanisms (n = 4). Empirical support was accrued for mediators such as anxiety, negative thinking, and mind-wandering, which are suggested to co-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
1
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 116 publications
(246 reference statements)
3
160
1
26
Order By: Relevance
“…Given that a growing awareness of racism is part of normative development (Garcia Coll et al, ), other scholars have investigated interventions for actively disrupting stereotype threat (e.g., Pennington, Heim, Levy, & Larkin, ; Taylor & Walton, ). A number of these studies have found that encouraging adolescents to either access an alternative, non‐stereotyped identity or affirm their identity in order to restore a positive self‐image can help mitigate the impact of stereotype threat (Croizet, Désert, Dutrévis, & Leyens, ; Taylor & Walton, ).…”
Section: Critical Consciousness and Academic Achievementmentioning
confidence: 99%
“…Given that a growing awareness of racism is part of normative development (Garcia Coll et al, ), other scholars have investigated interventions for actively disrupting stereotype threat (e.g., Pennington, Heim, Levy, & Larkin, ; Taylor & Walton, ). A number of these studies have found that encouraging adolescents to either access an alternative, non‐stereotyped identity or affirm their identity in order to restore a positive self‐image can help mitigate the impact of stereotype threat (Croizet, Désert, Dutrévis, & Leyens, ; Taylor & Walton, ).…”
Section: Critical Consciousness and Academic Achievementmentioning
confidence: 99%
“…For example, they are larger in young-older adults, aged 60–70 years, than in old-older adults, age 70+ years, and in more highly than less highly educated older adults [10]. A meta-analysis [2, 3] also revealed that domain identification, manipulation types of stereotype threat, and performance domain are important moderators. Aged-based stereotype threat effects are indeed stronger when domains are highly valued, when stereotype-based rather than fact-based manipulations are used, and when cognitive/memory rather than motor/skill performance are assessed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Stanford University, Stanford, CA, USA 2 Henan University, Henan, China studies to isolate how negative stereotypes about race, gender, and class interfere with performance (for a review of these studies, see Walton and Cohen 2003;Pennington et al 2016). Investigating stereotype threat in educational tracks helps establish whether stereotype threat operates only for certain kinds of stereotypes (such as those for race, gender, and class) and, if so, why.…”
Section: Research-article2018mentioning
confidence: 99%
“…These reminders lead to negative performance via several mechanisms (Pennington et al 2016;Schmader and Johns 2003), such as depleting working memory (Schmader, Johns, and Forbes 2008) or increasing mental load (Croizet et al 2004). For instance, Asian American women tend to do worse in mathematics when their gender identity is primed but not when their Asian identity is primed (Shih, Pittinsky, and Ambady 1999).…”
Section: Theoretical Framework: Stereotype Threatmentioning
confidence: 99%